36‐4: Full Color Active Matrix Video E‐Paper. Issue 1 (29th May 2019) - Henzen, Alex; Zhou, Guofu; Guo, Yuanyuan; Dou, Yingying; Jiang, Hongwei; Yang, Guisong; Tang, Biao
Abstract : E‐paper technology has evolved slowly since the introduction of monochrome electrophoretic displays, particularly in the field of color reproduction and video frame rate. We have now built a multilayer (cyan, magenta, yellow) electrowetting display, providing acceptable resolution for a 6", 262k color reflective video e‐paper display.